PENDIDIKAN DI INDONESIA DALAM TINJAUAN KONSEP PENDIDIKAN IBNU KHALDUN - Iis Faridah; Rizki Wahyu Yunian Putra (stit-islamic-village, 2023)
The purpose of this study is to find out how the concept of Ibn Khaldun's thinking and its relevance to education in Indonesia. Data collection using documentation. Data analysis used descriptive qualitative method, using literature research. The research results obtained by Ibn Khaldun classify science based on the material discussed in it and consider the usefulness of the science into: oral science (language), naqli science, and aqli science. An educator is someone who has broad knowledge and insight and has a good personality. A student is someone who is considered immature and has potential that can be developed. Thus, students need the help of adults to develop their potential. The learning methods offered by Ibn Khaldun include: the scientific rihlah method, the phasing and repetition method (tadarruj wat tikrari), and the general introduction method. The relevance of Ibn Khaldun's concept of thought to education in Indonesia, among others, is in terms of human insight in Indonesia, the goals of Islamic education, and the educational curriculum.